7 - The British Model, ‘Africanization’ of the Curriculum and Other Issues: The Influence of Professor D. W. Ewer (1913-2009) on University Teaching in Ghana and on Biological Education in Africa - Richard Alan Baker, (Journal of Higher Education in Africa, 2013)
Dennis William Ewer was Professor of Zoology during the formative years of tertiary education in Ghana and served as a distinguished academic in three African universities. In Ghana, he made an outstanding contribution to tropical biology and biology education. This historical account of one man’s attempt to improve the teaching of biology to African students is noteworthy for several reasons. He was an enormous influence for change in how and what biology was taught at both secondary and tertiary levels. Anxious for radical change and to break the mould of the Oxbridge tradition, he worked tirelessly to put an end to the British system of teaching biology and alter the course material to make it relevant in an African context. He believed that the transplantation of the British model was inappropriate for Africa. He emphasized the need and importance of training technicians and placed teaching before research in his priorities. In terms of the curriculum, ecology should, in his view, be the central integrating theme in Africa with a preferred slant towards applied biology rather than the pure science courses of the developed world. Ewer was also a prime mover for change at the secondary school level, helping to improve the biology syllabus, editing textbooks, and providing teacher’s guides. He was critical of the then current school teaching in biology because it bred passive students with bad work habits and believed there was a need to challenge students intellectually, both at school and university. This led him to clamour for new approaches in both secondary and higher education.